Accessory limb induction on flank region and its muscle regulation in axolotl. Issue 8 (11th June 2013) - Hirata, Ayako; Makanae, Aki; Satoh, Akira
<x xml:space="preserve">Abstract</x> Background : Urodele amphibians have high regeneration capability that has been studied for a long time. Recently, a new experimental system called the accessory limb model was developed and becomes alternative choice for amphibian limb regeneration study. Although the accessory limb model has many advantages, an improvement was needed for some specific analysis, such as studying muscle origin. For that purpose, an accessory limb induction on nonlimb regions was attempted. Results: Accessory limb induction on a nonlimb region (flank) was possible by nerve deviation and limb skin grafting. Retinoic acid injections improved the induction rate. The induced limb possessed the same tissue context as a normal limb. Muscle cells were also abundantly observed. It is speculated that the muscle cells are derived from flank muscle tissues, because limb muscle cells are a migratory cell population and the accessory limb was induced apart from the original limb. We also found that migration of the muscle cells was regulated by Hgf/cMet signaling as in other vertebrates. Conclusions: Accessory limb induction was possible even in the nonlimb flank region. The flank‐induced limb would be useful for further analysis of limb regeneration, especially for migratory cell populations such as muscle cells. Developmental Dynamics 242:932–940, 2013. © 2013 Wiley Periodicals, Inc.